The Influence of CEO Characteristics on the Corporate Gov-ernance Index (CGI) with Corporate Secretary Characteristics as a Moderating Variable - Moh. Baqir Ainun; Tyasha Ayu Melynda Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of CEO characteristics on the Corporate Governance Index (CGI) with the characteristics of the corpo-rate secretary as a moderating variable. The sample used is a company listed on the Indonesia Stock Exchange for the 2018-2022 period with a total of 939 observations. We offer novelty in the form of a combination of Shahwan's (2015) and Al-Hadi et al's (2017) CGI measurements to com-plement the shortcomings of both measurements and produce better re-search results and reduce bias. The data analysis used to answer the hy-pothesis is moderating regression analysis. The results showed that the characteristics of CEO age and CEO tenure had a significant effect on CGI. The characteristic of corporate secretary age is proven to moderate the effect of CEO age on CGI. The characteristics of corporate secretary tenure are proven to moderate the influence of CEO tenure on CGI. This research adds to the literature on CEO characteristics, characteristics of corporate secretaries and CGI, and provides important information that corporate secretaries need to pay attention to.